2022
DOI: 10.3389/fphar.2022.997598
|View full text |Cite
|
Sign up to set email alerts
|

Natural products of traditional Chinese medicine treat atherosclerosis by regulating inflammatory and oxidative stress pathways

Abstract: Atherosclerosis (AS) is a prevalent arteriosclerotic vascular disease that forms a pathological basis for coronary heart disease, stroke, and other diseases. Inflammatory and oxidative stress responses occur throughout the development of AS. Treatment for AS over the past few decades has focused on administering high-intensity statins to reduce blood lipid levels, but these inevitably damage liver and kidney function over the long term. Natural medicines are widely used to prevent and treat AS in China because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 112 publications
(92 reference statements)
1
2
0
Order By: Relevance
“…When reperfusion injury occurs, the expression of pro-inflammatory factors, adhesive molecules, cytokines, and chemokines can also be up-regulated and then induce cell apoptosis. Our results also suggest that serum TNF-α, IL-6 and IL-1β levels were immediately upregulated at the beginning of reperfusion and subsequently decreased, but the levels of these inflammatory cytokines still remained higher than those in the sham group until 24 h. Many studies suggest that TLR4 signaling pathway plays an important role in the transmission of inflammatory signals [ 32 , 33 ]. A large number of pro-inflammatory factors, chemokines and adhesion factors interact with TLR4 to promote the development of the disease [ 34 ].…”
Section: Discussionsupporting
confidence: 62%
“…When reperfusion injury occurs, the expression of pro-inflammatory factors, adhesive molecules, cytokines, and chemokines can also be up-regulated and then induce cell apoptosis. Our results also suggest that serum TNF-α, IL-6 and IL-1β levels were immediately upregulated at the beginning of reperfusion and subsequently decreased, but the levels of these inflammatory cytokines still remained higher than those in the sham group until 24 h. Many studies suggest that TLR4 signaling pathway plays an important role in the transmission of inflammatory signals [ 32 , 33 ]. A large number of pro-inflammatory factors, chemokines and adhesion factors interact with TLR4 to promote the development of the disease [ 34 ].…”
Section: Discussionsupporting
confidence: 62%
“…The JAK–STAT pathway is involved in almost all immunomodulatory processes and is a common pathway for a variety of cytokines and growth factors ( 78 ). IL-17 and IFN-γ activate TYK2 and JAK1 heterodimers.…”
Section: Iκbζ Is Induced Via Inflammatory Signal P...mentioning
confidence: 99%
“…Traditional Chinese medicine is extensively used in clinical settings due to its minimal toxicity and low side effects [87]. In a clinical study, it was found that the Yiqi Huaju Qingli formula had a positive effect on patients with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%